Black Power Inc.: The New Voice of Success - Daniels Cora (Wiley, 2004)
Black Power Inc. explores the emergence of a new black elite that sees business and economics as the true base of American power, rather than politics. Instead of mobilizing voters, they are storming boardrooms across the country and establishing themselves in positions of real influence. Now, Fortune magazine writer Cora Daniels, one of the primary chroniclers of this new shift in attitudes, reveals both the professionals who drive it and their motivations for doing so.